Trend and factors associated with delayed sputum conversion among elderly with smear-positive pulmonary tuberculosis in peninsular Malaysia from 2015 – 2024 - Zulkifli, Zainal (2025)
Background: Tuberculosis (TB) remains a major public health concern in Malaysia, with the elderly population disproportionately affected due to age-related immunosenescence, comorbidities, and social vulnerabilities. Delayed sputum conversion (DSC), defined as the persistence of sputum smear positivity beyond the two-month intensive phase, is a critical marker of poor treatment response, ongoing infectiousness, and increased risk of drug resistance. Despite these concerns, research on DSC among Malaysia's elderly remains limited. Objectives: This study aimed to examine trends and identify factors associated with DSC among elderly patients (aged ≥60 years) with smear-positive pulmonary TB (PTB) in Peninsular Malaysia from 2015 to 2024. Methods: A comparative cross-sectional study was conducted using secondary data from the National Tuberculosis Registry (NTBR). For trend analysis, all 15,736 elderly smear-positive PTB cases registered from 2015 to 2024 were included. For analytical purposes, 1,620 patients (810 with DSC and 810 with timely conversion) were selected via proportionate stratified random sampling. Descriptive analysis as well as simple and multiple logistic regression were conducted using SPSS Version 29. Results: The overall prevalence of DSC among elderly patients was 8.83%, with a notable increase from 6.87% in 2015 to 12.95% in 2024. Descriptive analysis showed that most patients were aged 60–74 years (82.6%), male (74.0%), and of Malay ethnicity (66.5%). Diabetes mellitus (43.7%) and smoking (34.0%) were common comorbidities. Multiple logistic regression identified significant predictors of DSC: rural residency (AdjOR=1.49, 95% CI: 1.20–1.84), diabetes mellitus (AdjOR=1.30, 95% CI: 1.05–1.61), advanced chest X-ray lesions (AdjOR=3.31, 95% CI: 1.50–7.32), relapse TB cases (AdjOR=1.77, 95% CI: 1.12–2.78), poor DOTS adherence (AdjOR=3.63, 95% CI: 2.20–5.99), and current smoking (AdjOR=1.28, 95% CI: 1.02–1.60). The final model showed modest discrimination (AUC = 62.3%). Conclusion: DSC among elderly TB patients in Malaysia has shown a rising trend, particularly after 2020, and is influenced by a combination of sociodemographic, clinical, treatment-related, and lifestyle factors. These findings call for targeted interventions to strengthen adherence support, especially among diabetics, relapse cases, and rural residents. Implementation of community-based DOTS (CB-DOTS), enhanced radiographic screening, and integrated tobacco cessation programs are critical to improving bacteriological response and achieving national TB control targets under the National Strategic Plan to End TB 2021–2030.